Professionalization as a method of removing the causes of professional burnoutand deformation of the person (Journal of Economic Research & Business Administration, 2017)
The article deals the problem of professional burnout. In recent years, more and more talk about the syndrome of professional combustion or burnout of workers. As a single cause of burnout, one can call a high level of claims among social workers. When highly motivated professionals fail to achieve their goals and feel that they can not make a significant contribution, they experience burnout. Unlike professional deformation, mental burnout can be attributed more to the case of complete regression of professional development, as it affects the personality as a whole, destroying it and adversely affecting the efficiency of work. An analysis of the conducted studies shows that such variables as age, marital status, length of service, do not affect emotional burnout. Women develop emotional exhaustion than men, they do not have a connection between motivation and development of the syndrome in the presence of a connection with the significance of work as a motive of activity, satisfaction with professional growth. The article also analyzes the problem of professional deformation that violates the integrity ofthe individual. The causes of this problem are age changes, professional deformations, professional fatigue,professional development crises, etc.